ASP.NET 3.5 : a beginner's guide - Sanders, William B., 1944- 4 0 16; 5 (New York : McGraw-Hill, 2009)
A guide to using the Web application framework Asp.net 3.5 that covers HTML forms, Web controls, SQL, data binding, LINQ, files, security, and other related topics.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Active server pages.;Active server pages; Microsoft .NET.;Web site development.;Microsoft .NET.;Computer programming; 20; 2